Engineering single-atomic ruthenium catalytic sites on defective nickel-iron layered double hydroxide for overall water splitting - Panlong Zhai (Nature Portfolio, 2021)
Rational design of single atom catalyst is critical for efficient sustainable energy conversion. Single-atomic-site ruthenium stabilized on defective nickel-iron layered double hydroxide nanosheets achieve superior HER and OER performance in alkaline media.